(untitled) (Revista Contexto & Saúde, 2025)
Understanding nurses’ perceptions of the ethical climate based on their experiences of moral distress in the face of ethical and moral conflicts encountered in the hospital setting. This is a qualitative, exploratory-descriptive study conducted with 20 nurses working in psychiatry, emergency care, surgical clinic, and obstetric center of a university hospital in southern Brazil. Data collection took place between August and October 2021 through semi-structured interviews. Discursive textual analysis was employed. Two categories emerged: the first, “The ethical climate in the hospital setting” addressed aspects related to weaknesses and conflicts in care, interpersonal relationships, and management based on hierarchical structures; the second, “Moral sensitivity fostering an ethical climate in nursing practice”, referred to patient rights advocacy, organizational policies and practices, and professional recognition and appreciation. Moral sensitivity and effective communication are key elements for a positive ethical climate, as they promote an appropriate care environment and contribute to the defense of patient rights.